The Practices Of Takaful Al-ijtimai’ During Covid-19: Malaysia’s Setting - Junaidah Abu Seman; Hisham Sabri; Wan Nur Fazni Wan Mohamad Nazarie; Nur Adilah Othman (USIM Press, 2024)
Every aspect of human life is inherently risky. The fatal infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), known as coronavirus disease 2019 (COVID-19), has been considered a black swan event and compared to the economic scene of World War Two. The concept and practices of takaful al-ijtimai’ or social security are pertinent area to be discussed amidst the COVID-19 pandemic recovery mission because its meaning and applications are much wider; encompasses both financial and non-financial assistance and is not limited by the country's regulations. Using secondary data, this study will examine the concept and scopes of takaful al-ijtimai’, from an Islamic perspective, as well as provide the current state of the art in its application during the COVID-19 epidemic in Malaysia. The study is intended to contribute to an understanding and promotion of the concept of takaful al-ijtimai’ as an important tool for achieving maqasid shariah and sustainable development goals.